INFUSION MONITORING SYSTEM FOR PATIENTS BASED ON THE INTERNET OF THINGS (IOT) WITH ANDROID NOTIFICATION SYSTEM - Akbar Sujiwa; Risqi Rahmat Dianto (BEST, 2022)
Infusion is one of the medical needs that are needed by many patients in various hospitals or health centers. Infusion is a way in which a patient can introduce fluids or drugs into the body quickly or slowly and continuously. Therefore, nurses always monitor the infusion manually and periodically to ensure the condition of the infusion fluid. The experimental method used in this study was by adding several features to make it easier for nurses to monitor patient infusions. The Infusion Monitoring System device used is based on the Internet of Things (IoT) with the Android Notification System. This research is expected to be able to monitor infusions more practically and can be monitored mobile using cellphones anywhere and anytime. To present this tool in this study, the author uses Nodemcu used to process data and also serves to connect to the internet. Then the sensors used are the Load cell sensor as a measuring tool for infusion volume and the Photodiode sensor as a detection tool for infusion fluid droplets. Then the calculation data from the sensor is sent to Firebase which acts as a database, and later it will be accessible and monitored via mobile phones through an android application created by the researcher. From the test results of the tools that the researcher made and the testing of comparison tools. The average of these tests gets an accuracy difference of approximately 2%. (Abstract)